2009
DOI: 10.1101/cshperspect.a001891
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Breaking During Drosophila Oogenesis

Abstract: The orthogonal axes of Drosophila are established during oogenesis through a hierarchical series of symmetry-breaking steps, most of which can be traced back to asymmetries inherent in the architecture of the ovary. Oogenesis begins with the formation of a germline cyst of 16 cells connected by ring canals. Two of these 16 cells have four ring canals, whereas the others have fewer. The first symmetry-breaking step is the selection of one of these two cells to become the oocyte. Subsequently, the germline cyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 130 publications
(143 reference statements)
1
139
0
Order By: Relevance
“…Furthermore, this work posits that each cyst present at the time of meiotic onset produces a single oocyte, which is quite similar to dynamics of oocyte and nurse cell production in Drosophila. Importantly, however, mammalian cysts are fragmented completely early in development, with the ovary possessing only intact follicles during adulthood (Lei and Spradling, 2013b); this is in contrast to Drosophila cysts, which are formed and utilized throughout the life of the animal (Roth and Lynch, 2009). Interestingly, it was also demonstrated that mouse oocytes possess a Balbiani body, or mitochondrial cloud of organelles localized next to the developing oocyte nucleus .…”
Section: A Timeline Of Mammalian Primordial Follicle Developmentmentioning
confidence: 99%
“…Furthermore, this work posits that each cyst present at the time of meiotic onset produces a single oocyte, which is quite similar to dynamics of oocyte and nurse cell production in Drosophila. Importantly, however, mammalian cysts are fragmented completely early in development, with the ovary possessing only intact follicles during adulthood (Lei and Spradling, 2013b); this is in contrast to Drosophila cysts, which are formed and utilized throughout the life of the animal (Roth and Lynch, 2009). Interestingly, it was also demonstrated that mouse oocytes possess a Balbiani body, or mitochondrial cloud of organelles localized next to the developing oocyte nucleus .…”
Section: A Timeline Of Mammalian Primordial Follicle Developmentmentioning
confidence: 99%
“…Similar to C. elegans, D. melanogaster also uses actin for embryonic polarization, however, the cue in this case is not sperm entry but inductive signaling and asymmetric transport of maternal mRNAs during oogenesis-there is no evidence for anterior-directed contractile cortical flow; reviewed in [273,274]. The cortical actin network is however directly responsible for localization of the polarity factor Par1 [275] and together with polarized localization of the polarity regulator Cdc42 involved in oocyte polarization through positive feedback onto the Par3/Par6/aPKC polarity complex [276].…”
Section: Actomyosinmentioning
confidence: 99%
“…Since the Drosophila DV patterning gene regulatory network (GRN) is the gold standard to which other insects will be compared, crucial aspects of the functioning of this network are described here (for more in depth review, see Roth 2003; Moussian and Roth 2005;Hong et al 2008;Roth and Lynch 2009). The cascade of molecular interactions that lead to the establishment of cell fates along the DV axis of the Drosophila embryo begins with a symmetry-breaking event in the ovary, when the oocyte nucleus moves to a cortical position that is asymmetric with regard to the short axis of the egg chamber (Roth and Lynch 2009).…”
Section: Setting Up the DV Axis In Drosophilamentioning
confidence: 99%
“…The cascade of molecular interactions that lead to the establishment of cell fates along the DV axis of the Drosophila embryo begins with a symmetry-breaking event in the ovary, when the oocyte nucleus moves to a cortical position that is asymmetric with regard to the short axis of the egg chamber (Roth and Lynch 2009). mRNA for gurken (grk) is localized around the oocyte nucleus and translated, and its protein (encoding a tgf-a-like EGF ligand) is secreted to the overlying somatic follicle cells, where it activates the EGF receptor (EGFR) ( Fig.…”
Section: Setting Up the DV Axis In Drosophilamentioning
confidence: 99%